2018
DOI: 10.3390/app8112278
|View full text |Cite
|
Sign up to set email alerts
|

Smart Grid Testing Management Platform (SGTMP)

Abstract: The Smart Grid (SG) is nowadays an essential part of modern society, providing two-way energy flow and smart services between providers and customers. The main drawback is the SG complexity, with an SG composed of multiple layers, with devices and components that have to communicate, integrate, and cooperate as a unified system. Such complexity brings challenges for ensuring proper reliability, resilience, availability, integration, and security of the overall infrastructure. In this paper, we introduce a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Testing in the context of smart grids is extremely complex due to the multi-layer structure of the overall infrastructure [4]. In addition, smart grid testing involves the integration with hardware devices, making use of modeling and simulations highly relevant to discovering integration issues at scale [8], [9]. The testing chain is a series of experiments (from pure simulation to actual field-testing) used to develop a new component reducing the risk of failure or to validate a component with an holistic approach cost effectively.…”
Section: Overview Of the Testing Chain Methodologymentioning
confidence: 99%
“…Testing in the context of smart grids is extremely complex due to the multi-layer structure of the overall infrastructure [4]. In addition, smart grid testing involves the integration with hardware devices, making use of modeling and simulations highly relevant to discovering integration issues at scale [8], [9]. The testing chain is a series of experiments (from pure simulation to actual field-testing) used to develop a new component reducing the risk of failure or to validate a component with an holistic approach cost effectively.…”
Section: Overview Of the Testing Chain Methodologymentioning
confidence: 99%
“…In our review, we found that 59% of the articles had some form of interaction with hardware devices. We expect that with the explosion of the IoT movement and the large availability of commodity hardware such as Arduinos and Raspberry PIs, such trend will increase, allowing hybrid simulations to take place in this context, as recent research has already shown-Schvarcbacher & Rossi (2017); Schvarcbacher et al (2018), (Nannen et al, 2015).…”
Section: Research Directionsmentioning
confidence: 99%
“…The complexity of smart grid and smart city architectures brings many challenges and issues, especially when it comes to reliability, resilience, integration and security of the whole infrastructure. Therefore, the approach of software modelling and simulation can be highly beneficial in process of testing of such applications and mechanisms before the actual deployment to ensure proper operation in all scenarios without high costs [38,39]. Data-driven Architecture for Energy-Efficient Smart Cities…”
Section: Simulation Toolmentioning
confidence: 99%